Jenis-Jenis Burung Air Di Hutan Mangrove Kecamatan Paloh Kabupaten Sambas - Ari Hepi Yanti, Muhammad Suriansyah, Tri Rima Setyawati (Universitas Tanjungpura, 2016)
The reduced in the area of mangrove forests are feared will cause a decrease of wildlife that exists, one of which is a water birds. This research aims to find out the species of water birds in mangrove forest Mutusan River, Subdistrict of Paloh. This research was carried out during the three months from February to April2015. The data species of water birds are collected using IPA (Index Point of Abundance) method. The number of water birds species found throughout the research area as many as 19 species in 8 families. We are found a high species are found in family Ardeidae i.e Ardeola bacchus, Butorides striatus, Egretta alba, E. garzetta, E. sacra.